2015
DOI: 10.1111/bph.13180
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A receptors are necessary and sufficient to trigger memory impairment in adult mice

Abstract: BACKGROUND AND PURPOSECaffeine (a non-selective adenosine receptor antagonist) prevents memory deficits in aging and Alzheimer's disease, an effect mimicked by adenosine A2A receptor, but not A1 receptor, antagonists. Hence, we investigated the effects of adenosine receptor agonists and antagonists on memory performance and scopolamine-induced memory impairment in mice. EXPERIMENTAL APPROACHWe determined whether A2A receptors are necessary for the emergence of memory impairments induced by scopolamine and whet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
45
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(50 citation statements)
references
References 66 publications
(94 reference statements)
0
45
0
2
Order By: Relevance
“…Several studies have previously shown that A 2A R blockade prevents memory deficits associated with chronic stress or depression (Batalha et al, ; Cunha et al, ; Kaster et al, ; Machado et al, ). These studies focused on the relation between synaptic dysfunction and memory deterioration and have shown that neuronal A 2A R were both necessary and sufficient to trigger memory deficits (Li et al, ; Pagnussat et al, ; Viana da Silva et al, ). Although the blockade of A 2A R is globally accepted as a cognitive enhancer and anxiolytic, in animal models of disease, the majority of the studies were performed in males or the gender was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously shown that A 2A R blockade prevents memory deficits associated with chronic stress or depression (Batalha et al, ; Cunha et al, ; Kaster et al, ; Machado et al, ). These studies focused on the relation between synaptic dysfunction and memory deterioration and have shown that neuronal A 2A R were both necessary and sufficient to trigger memory deficits (Li et al, ; Pagnussat et al, ; Viana da Silva et al, ). Although the blockade of A 2A R is globally accepted as a cognitive enhancer and anxiolytic, in animal models of disease, the majority of the studies were performed in males or the gender was not specified.…”
Section: Discussionmentioning
confidence: 99%
“…), the pharmacological activation of A 2A R in the hippocampus (Pagnussat et al . ) or cingulate cortex (Pereira et al . ) or the optical activation of the A 2A R transducing system in the hippocampus (Li et al .…”
Section: The Role Of A2ar In Neuroprotectionmentioning
confidence: 99%
“…Caffeine consumption, which is an A2ARs antagonist, prevented the STZ-induced memory impairment and neuronal damage [207]. Similarly, Pagnussat et al studied the effect of caffeine on A2ARs for revoking the cognitive impairments in scopolamine-induced neurodegenerative mice and found the reversal of cognitive deficits with the caffeine [208]. …”
Section: Neurotransmitter-based Therapeutics In Admentioning
confidence: 99%